Altered Amygdala Connectivity in Individuals with Chronic Traumatic Brain Injury and Comorbid Depressive Symptoms - Han, Kihwan; Chapman, Sandra B.; Krawczyk, Daniel C. (Frontiers in Neurology, 2015)
Depression is one of the most common psychiatric conditions in individuals with chronic Traumatic Brain Injury (TBI). Though depression has detrimental effects in TBI and network dysfunction is a 'hallmark' of TBI and depression, there have not been any prior investigations of connectivity-based neuroimaging biomarkers for comorbid depression in TBI. We utilized resting-state functional magnetic resonance imaging to identify altered amygdala connectivity in individuals with chronic TBI (eight years post-injury on average) exhibiting comorbid depressive symptoms (N=31), relative to chronic TBI individuals having minimal depressive symptoms (N=23). Connectivity analysis of these participant sub-groups revealed that the TBI-plus-depressive symptoms group showed relative increases in amygdala connectivity primarily in the regions that are part of the salience, somatomotor, dorsal attention and visual networks (pvoxel<0.01, pcluster<0.025). Relative increases in amygdala connectivity in the TBI-plus-depressive symptoms group were also observed within areas of the limbic-cortical mood-regulating circuit (the left dorsomedial and right dorsolateral prefrontal cortices and thalamus) and the brainstem. Further analysis revealed that spatially-dissociable patterns of correlation between amygdala connectivity and symptom severity according to subtypes (Cognitive and Affective) of depressive symptoms (pvoxel<0.01, pcluster<0.025). Taken together, these results suggest that amygdala connectivity may be a potentially effective neuroimaging biomarker for comorbid depressive symptoms in chronic TBI.